AN APPRAISAL OF THE CONTRIBUTION OF IMAM AL-TABARI TO THE ISLAMIC HISTORIOGRAPHY - Zayyanu Altine (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
Tabari's work was a World history or a comprehensive history, covering the history of a vast time frame. He consciously kept a chronological scheme of events in his book. He presented the evidence of historical facts, and tried to remain as much objective as possible. He presented elaborate details on the life of the Prophet (S.A.W). While writing' the history of controversial historical events, he devised a new method of narrating all the conflicting versions and then leaving the judgment to the readers. The aim and objectives of this paper is to examine al Tabari's brief biography and contributions towards historiography being him as a Muslim scholar in a tremendous braches of knowledge including history among others. Analytical method is employed when conducting the research. The paper finds out and ascertained some incessant and essential contributions given by the Al-Tabari to the historiography as well. Last but not the list the paper made recommendations and concluded.